Consumer response to different advertising appeals: The role of brand value and the perceptual fit of an extended brand for high-involvement products - Rosa Prafitri Juniarti; Adi Zakaria Afiff (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2020)
Brand extension is a topic that has been widely discussed by academics and practitioners in various studies. Unfortunately, there are only a few that address the role of product involvement, advertising appeals, and value dimensions in the extension acceptance as their main issue. Therefore, this study aims to mixed three controlling factors which are product involvement, advertising appeals, and brand value dimensions in determining how consumers respond to the parent brand and extended brand. This study was designed to test the possible interaction in a 2x2x2 full-factorial between advertising appeals (informational vs. emotional), brand extension perceived fit (high vs. low), and value dimension (symbolic vs. functional) for high involvement products. This study confirmed that there were significant differences in the main effects for both consumers' evaluation toward brand extension and the parent brand in the case of a symbolic brand and the high fit of extensions. Emotional appeals play important role in enhancing this degree because of the high level of its brand associations. As symbolic brand often referred as premium brand, the more positive the level of quality perception, the higher level of consumers' evaluation toward brand and brand loyalty will be. Thus, the more loyal consumer to the parent brand, the more positive evaluations of the extension will be.